Implementation of a Diversity Corner to Enhance Elementary School Students’ Social Skills - Sari, Fransiska Faberta Kencana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
Social skills are essential competencies that need to be developed in elementary school students to support positive social interaction, cooperation, and respect for diversity in everyday life. However, classroom learning practices indicate that students’ social skills, particularly in terms of cooperation, empathy, and interpersonal communication, still require improvement. This study aims to analyze the implementation of a Diversity Corner as a learning strategy to enhance elementary school students’ social skills. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. The research stages included planning the Diversity Corner, implementing diversity-based learning activities, and evaluating the development of students’ social skills. The results indicate that the implementation of a Diversity Corner creates an inclusive and participatory learning environment. Students demonstrated improvements in cooperation, empathy, and positive interpersonal communication skills. Therefore, the implementation of a Diversity Corner contributes positively as a contextual learning strategy in fostering elementary school students’ social skills.